A scoping review of the prevalence of use of substance among African, Caribbean, and Black (ACB) people in Canada. (1st November 2020) - Nguemo Djiometio, Joseph Bertrand; Buzuayew, Asfaw; Nelson, LaRon E; Maina, Geoffrey; Njoroge, Irene; Kahan, Meldon; Wong, Josephine
ABSTRACT: In Western countries, Blacks experience various challenges and problems such as discrimination, racism, unemployment, low income that can contribute to substance use. This scoping review seeks to map available evidence on the prevalence, factors associated and impacts for substance use among ACB people in Canada. We searched electronic bibliographic databases including Ovid MEDLINE, PsycINFO, and CINAHL, and also conducted a gray literature search. Our search strategy yielded 676 references, of which 25 were included in the review. The overall prevalence of substance use varied substantially. ACB people use cannabis (12–40%), alcohol (65–100%), tobacco (5–27%) and hallucinogens (4%). In addition, ACB people use polydrug. Key factors associated with increased substance use included low income, economic deprivation, unemployment, social networks, lack of health education, immigration and stressor factors, discrimination, and limited access to treatment services. Substance use was associated with various social impacts such as high rates of school drop-out, unemployment, family violence and disruption, financial problems, driving under the influence of alcohol, criminalization, and stigmatization toward alcohol use. Besides, substance use can lead to health issues such as HIV risk behaviors, risky sexual intercourse, addiction, overdose, and substance use disorders.